PENGARUH E-TRUST, E-SATISFACTION, DAN PERCEIVED VALUE TERHADAP REPURCHASE INTENTION PADA KONSUMEN E-COMMERCE B2C COFFEE SHOP - Kamiilah Ulayya; Willy Arafah (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study examines the influence of e-trust, e-satisfaction, and perceived value on repurchase intention among B2C e-commerce coffee shop consumers. The research uses a survey method with a sample of 200 respondents who have made purchases on B2C e-commerce coffee shop platforms. Data were analyzed using structural equation modeling. The results show that e-trust and perceived value have a positive and significant effect on repurchase intention, while e-satisfaction does not have a significant effect. Prior online experience strengthens the relationships between e-trust, perceived value, and repurchase intention. These findings suggest that e-commerce coffee shop businesses should focus on building trust and offering high perceived value to encourage repeat purchases. Providing a positive online experience can further enhance the impact of e-trust and perceived value on repurchase intention